The Spanish coastal systems – Dynamic processes, sediments and management - van Loon, A.J. Tom (Geologos, 2019)
Book review: The Spanish coastal systems – Dynamic processes, sediments and management, by Juan A. Morales (Ed.), 2019. Springer Nature Switzerland. xiv + 823 pages. Hardback: price $179.99, ISBN 978-3-319-93168-5. E-book: price $139.00, ISBN 978-3-319-93169-2.